Cross-Border Banking and Transmission Mechanisms: The Case of Europe - Claudia M. Buch (Kiel Institute of World Economics (IfW), 2001)
International activities of commercial banks are a potential source for the transmission of shocks across countries. In Europe, bank finance plays a relatively important role, and efforts have been made at creating a level playing field for financial institutions. This paper reviews the stylized facts of the integration of European banking markets and the changing nature of cross-border banking. Although the openness of financial systems has increased, bilateral financial linkages among EU countries remain relatively small. The exception are claims of German banks on a number of smaller countries, and we use these data for an analysis of the determinants of cross-border lending patterns.
Keywords: G15; F42; F36; 330; cross-border banking; European integration; transmission of shocks; Finanzmarkt; Bank; Internationale Bank; Marktintegration; Internationale Kreditvergabe; Internationale Kapitalmobilität; Währungsunion; Europäische Wirtschafts- und Währungsunion; Transmissionsmechanismus; Konjunkturzusammenhang; Schätzung